In vitro propagation of XXY human Klinefelter spermatogonial stem cells: A step towards new fertility opportunities - Galdon, Guillermo; Deebel, Nicholas A.; Zarandi, Nima Pourhabibi; Teramoto, Darren; Lue, YanHe; Wang, Christina; Swerdloff, Ronald; Pettenati, Mark J.; Kearns, William G.; Howards, Stuart; Kogan, Stanley; Atala, Anthony; et al. (Frontiers in Endocrinology, 2022)
Klinefelter Syndrome (KS) is characterized by masculine phenotype, supernumerary sex chromosomes (47, XXY), and impaired fertility due to loss of spermatogonial stem cells (SSCs). Early testicular cryopreservation could be an option for future fertility treatments in these patients, including SSCs transplantation or in vitro spermatogenesis. Adapting current in vitro SSCs propagation systems for KS patients is critically essential. Patients enrolled in an experimental testicular tissue banking program donated KS human testicular samples (13,15- and 17-year-old non-mosaic KS boys). Testicular cells were isolated from cryopreserved tissue and propagated in long-term culture for 110 days. Cell-specific gene expression confirmed the presence of all four main cell types expected in testes: Spermatogonia, Sertoli, Leydig, and Peritubular cells. A population of ZBTB16+ undifferentiated spermatogonia was identified throughout the culture using digital PCR. Flow Cytometry analysis detected an HLA-/CD9+/CD49f+ population, suggesting a stem cell subpopulation during the culture. FISH staining for chromosomes X and Y showed most cells in culture containing XXY combination and a small number with either XY or XX cells. Both XY and XX populations were enriched by Magnetic sorting for CD9 as a spermatogonia marker. Molecular Karyotyping showed the genome stability of 47 XXY cells in the culture. Finally, single-cell RNAseq analysis identified a cluster of ID4, TCN2, and NANOS 3 positive cells representing a putative SSCs population. This is the first study showing successful isolation and long-term in vitro propagation of human KS testicular cells. These findings could potentially impact therapeutic fertility options for KS patients either by spermatogenesis in vitro or transplantation of SSCs in vivo.